PUSAT PENANGGULANGAN BENCANA KABUPATEN SINTANG - Gaudensius Waldi Fernando; Emilya Kalsum; Jawas Dwijo Putro (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2021)
Natural conditions as well as the diversity of population and culture in Indonesia cause the risk of natural disasters, social disasters and complex emergencies to arise. The implementation of emergency response is also often not supportive, the distribution of aid and services is not fast, uneven and difficult to monitor properly, so that the progress of the results of disaster emergency response activities is less objectively measurable. In Sintang Regency, in addition to natural disasters, social disasters also often occur, because the facilities are not standardized and accommodated so that services are not optimal. Judging from the existing needs, the Disaster Management Center is a facility that can assist the implementation of Disaster Emergency Response activities in Sintang Regency. The Disaster Management Center can accommodate disaster emergency response activities so that it has strategic command lines so that information confusion can be minimized so as to realize appropriate policies in dealing with disasters. The planned Disaster Management Center is a facility that functions to accommodate agencies related to pre- and post-disaster management, both as a place for disaster management and as an information center. The design method for this Disaster Management Center uses a comparison of literatures and performs data processing to describe the design process of the Sintang Regency Disaster Management Center. The mass of the building is divided into three parts separated by function and purpose. The approach to design applies an integrated concept, referring to a standardized and accommodating spatial layout.